Analyzing the Usefulness of ThingFO as a Foundational Ontology for Sciences - Olsina Santos, Luis Antonio (2020)
This work specifies and defines all terms, properties and relationships of ThingFO –which stands for Thing Foundational Ontology. ThingFO is an ontology for particular and universal Things and Assertions placed at the foundational level in the context of a four-layered ontological architecture called FCDOntoArch. This is a four-layered ontological architecture, which considers foundational, core, domain and instance levels. In turn, the domain level is split down into two sub-levels, namely: top-domain and low-domain. Ontologies at the same level can be related to each other, except for the foundational level where only the ThingFO ontology is. Additionally, ontologies' terms, properties and relationships at lower levels can be semantically enriched by ontologies' terms properties and relationships from the higher levels. Since ThingFO is at the highest level, ontologies at lower levels benefit from reusing and extending its concepts. To illustrate the usefulness of ThingFO, we primarily analyze enriched terms of a couple of ontologies at the core level such as ProcessCO and SituationCO, among others, in which their concepts are cross-cutting concerns for many domain terminologies from diverse sciences.